2023
DOI: 10.1021/acsphotonics.3c00033
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Origin of Light Intensity and Temperature Dependence of Photodetection Properties in a MAPbBr3 Single-Crystal-Based Photoconductor

Abstract: Methylammonium lead bromide (MAPbBr3), which belongs to the larger material family of lead halide perovskites (LHPs), has emerged as a promising semiconductor for the fabrication of single-crystal (SC)-based photodetectors (PDs). However, there is still a lack of sufficient understanding of the effect of irradiation power and applied temperature on the photodetection performance of SC-based perovskite PDs. Here, we investigate the impact of different light intensities and temperatures on the photodetection pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 58 publications
2
25
0
Order By: Relevance
“…The increased current rapidly decreases under illumination but stabilizes before decaying to the off state. In our recent work, we have demonstrated that accumulation of surface defects influences the contact–SC interface band bending, which causes the loss in photocurrent from the maximum value . Studies by Lafalce et al illustrate that the photocurrent response in MAPbBr 3 SC-based devices is mainly dominated by the surface charge effects generated by the accumulation of intrinsic ionic impurities such as Pb 2+ and Br .…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…The increased current rapidly decreases under illumination but stabilizes before decaying to the off state. In our recent work, we have demonstrated that accumulation of surface defects influences the contact–SC interface band bending, which causes the loss in photocurrent from the maximum value . Studies by Lafalce et al illustrate that the photocurrent response in MAPbBr 3 SC-based devices is mainly dominated by the surface charge effects generated by the accumulation of intrinsic ionic impurities such as Pb 2+ and Br .…”
Section: Resultsmentioning
confidence: 82%
“…The switching behavior in MAPbBr 3 single crystals in the lateral configuration (refer to Figure a) was investigated. Detailed information about the preparations of MAPbBr 3 single crystals, as well as their structural and optical properties, have been discussed in our previous works and in the Supporting Information (SI). The J – V response of MAPbBr 3 single crystals, measured in a bias range of −5 to 5 V, is shown in Figure b.…”
Section: Resultsmentioning
confidence: 99%
“…[ 42,43 ] A set of planar MAPbBr 3 SC PDs with various Pt electrode spacings was fabricated according to our recently published report (for details, see Experimental Section). [ 44 ]…”
Section: Resultsmentioning
confidence: 99%
“…To explain this contradictory behavior, we determined the power exponent β ( J ph ∝ P β , where P is irradiation power and β is a recombination‐related constant under illumination) from the logarithmic plot of photocurrent density ( J ph ) as a function of green light irradiation intensity for PDs with various electrode spacings. [ 44 ] As shown in Figure S5a, Supporting Information, the value of the exponent β increases with decreasing the electrode spacing, and its higher value indicates lower recombination and better charges collection efficiency, which helps to increase the J ph . [ 52 ] A similar trend was also observed for the power exponent β extracted from the logarithmic plot of J ph as a function of blue light irradiation intensity (Figure S5b, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…In order to evaluate the performance of the perovskite single crystal photodetectors, the responsivity ( R ), external quantum efficiency (EQE) and specific detection rate ( D ) are calculated as follows: 36 where I p and I d represent photocurrent and dark current, respectively, P in is the 405 nm laser power density, S is the effective area of the photodetector, h is the Planck constant, c is the speed of light, e is the electron charge, and λ is the laser wavelength. From Fig.…”
Section: Resultsmentioning
confidence: 99%